Reproductive assurance in three Neotropical species of Podostemaceae: strategies of self-pollination and the first report of apomixis1 - Inara Carolina da Silva-Batista; Cristiana Koschnitzke; Claudia Petean Bove (Hoehnea, 2020)
ABSTRACT (Reproductive assurance in three Neotropical species of Podostemaceae: strategies of self-pollination and the first report of apomixis). The aspects of reproductive assurance of the Lophogyne lacunosa (Gardner) C.P.Bove & C.T.Philbrick, Podostemum weddellianum (Tul.) C.T. Philbrick & Novelo, and Tristicha trifaria (Bory ex Willd.) Spreng. were investigated and, the mechanisms correlated to the flower morphology and floral biology. The mating system of L. lacunosa was also described, as well as the first report of apomixis in Podostemaceae. The reproductive assurance strategies used by L. lacunosa were autonomous competitive self-pollination, wind pollination, and apomixis. This species has floral attributes that ensure the dispersion of pollen by wind and its capture by the stigmas. Podostemum weddellianum and Tristicha trifaria presented autonomous competitive self-pollination before and during anthesis, respectively; both lack floral attributes for wind pollination. Considering that these species can be found in the same running water environment and that they are not phylogenetically close related, it was concluded that the different reproductive strategies are related to their evolutionary lineages.